N-Formyl peptides drive mitochondrial damage associated molecular pattern induced neutrophil activation through ERK1/2 and P38 MAP kinase signalling pathways. Issue 6 (June 2015) - Hazeldine, Jon; Hampson, Peter; Opoku, Francis Adusei; Foster, Mark; Lord, Janet M.
Abstract: Traumatic injury results in a systemic inflammatory response syndrome (SIRS), a phenomenon characterised by the release of pro-inflammatory cytokines into the circulation and immune cell activation. Released from necrotic cells as a result of tissue damage, damage associated molecular patterns (DAMPs) are thought to initiate the SIRS response by activating circulating immune cells through surface expressed pathogen recognition receptors. Neutrophils, the most abundant leucocyte in human circulation, are heavily implicated in the initial immune response to traumatic injury and have been shown to elicit a robust functional response to DAMP stimulation. Here, we confirm that mitochondrial DAMPs (mtDAMPs) are potent activators of human neutrophils and show for the first time that signalling through the mitogen-activated-protein-kinases p38 and extracellular-signal-related-kinase 1/2 (ERK1/2) is essential for this response. At 40 and/or 100 μg/ml, mtDAMPs activated human neutrophils, indicated by a significant reduction in the surface expression of l -selectin, and triggered a number of functional responses from both resting and tumour necrosis factor-α primed neutrophils, which included reactive oxygen species (ROS) generation, degranulation, secretion of interleukin-8 and activation of p38 and ERK1/2 MAPKs. Pre-treatment of neutrophils with Cyclosporin H, a selective inhibitor of formyl peptide receptor-1 (FPR-1), significantly inhibited mtDAMP-induced l -selectin shedding as well as p38 and ERK1/2 activation, suggesting that N -formyl peptides are the main constituents driving mtDAMP-induced neutrophil activation. Indeed, no evidence of l -selectin shedding or p38 and ERK1/2 activation was observed in neutrophils challenged with mitochondrial DNA alone. Interestingly, pharmacological inhibition of p38 or ERK1/2 either alone or in combination significantly inhibited l -selectin shedding and IL-8 secretion by mtDAMP-challenged neutrophils, revealing for the first time that MAPK activation is required for mtDAMP-induced neutrophil activation and function. Our findings demonstrate that signalling through FPR-1 and activation of p38 and ERK1/2 MAPKs are key events in mtDAMP-induced neutrophil activation. Gaining an understanding of the signalling pathways involved in mtDAMP-induced neutrophil activation may assist in the development of future therapeutic strategies aimed at targeting the SIRS response to improve the outcome of the hospitalised trauma patient. Reducing the severity of the inflammatory response may realise substantial benefits for the severely injured trauma patient.